Is There Any Advantage of Treating Partners in Helicobacter pylori Eradication?. (15th March 2015) - Rakici, Halil; Akdogan, Remzi Adnan; Ayaz, Teslime; Bedir, Recep
Abstract : Aim. We designed this trial to find answers to the following questions. (1) Does the success rate decrease in a country where HP prevalence is high? (2) Can we provide benefit by simultaneously treating the partners of infected patients? Materials and Methods. The first group consisted of 102 HP-positive patients, and both the patients and their HP-positive partners were treated. The second group consisted of 104 HP-positive patients whose partners were HP-positive but only the patients were treated. The participants in both groups were treated with levofloxacin 500 mg daily, amoxicillin 1 g b.i.d, and lansoprazole 30 mg b.i.d (LAL) for ten days. Results. In the per-protocol analysis, the eradication success rate was found to be 92.2% (94/8) in the first group and 90.4% (94/10) in the second group. No statistically significant difference was found between the two groups (P > 0.05 ). Conclusions. With regard to the HP eradication rate, no difference was found between treating the HP-positive partners of HP-positive patients simultaneously and not treating them simultaneously. According to these results, we can say that reinfections between partners do not significantly contribute to the failure of eradication.